Detection of Bartonella spp. in dogs after infection with Rickettsia rickettsii. (31st December 2019) - Lashnits, Erin; Neupane, Pradeep; Maggi, Ricardo G.; Linder, Keith E.; Bradley, Julie M.; Balakrishnan, Nandhakumar; Southern, Brittany L.; McKeon, Gabriel P.; Chandrashekar, Ramaswamy; Breitschwerdt, Edward B.
Abstract: Background: Dynamics of infection by Bartonella and Rickettsia species, which are epidemiologically associated in dogs, have not been explored in a controlled setting. Objectives: Describe an outbreak investigation of occult Bartonella spp. infection among a group of dogs, discovered after experimentally induced Rickettsia rickettsii ( Rr ) infection. Animals: Six apparently healthy purpose‐bred Beagles obtained from a commercial vendor. Methods: Retrospective and prospective study. Dogs were serially tested for Bartonella spp. and Rr using serology, culture, and PCR, over 3 study phases: 3 months before inoculation with Rr (retrospective), 6 weeks after inoculation with Rr (retrospective), and 8 months of follow‐up (prospective). Results: Before Rr infection, 1 dog was Bartonella henselae ( Bh) immunofluorescent antibody assay (IFA) seroreactive and 1 was Rickettsia spp. IFA seroreactive. After inoculation with Rr, all dogs developed mild Rocky Mountain spotted fever compatible with low‐dose Rr infection, seroconverted to Rickettsia spp. within 4‐11 days, and recovered within 1 week. When 1 dog developed ear tip vasculitis with intra‐lesional Bh, an investigation of Bartonella spp. infection was undertaken. All dogs had seroconverted to 1‐3 Bartonella spp. between 7 and 18 days after Rr inoculation. Between 4 and 8 months after Rr inoculation, Bh DNA was amplified from multiple tissues from 2 dogs, and Bartonella vinsonii subsp. berkhoffii ( Bvb ) DNA was amplified from 4 of 5 dogs' oral swabs. Conclusions and Clinical Importance: Vector‐borne disease exposure was demonstrated in research dogs from a commercial vendor. Despite limitations, our results support the possibilities of recrudescence of chronic subclinical Bartonella spp. infection after Rr infection and horizontal direct‐contact transmission between dogs.